Neuroendocrine Mechanisms for Immune System Regulation During Stress in Fish - Imarai-Bahamonde, C; Montoya-Kunsting, M; Acuna-Castillo, C; Jara-Picas, P; Valenzuela-Montenegro, B (2014)
Sin Editorial Disponible